Use of Severity Grades to Characterize Histopathologic Changes. (April 2018) - Schafer, Kenneth A.; Eighmy, John; Fikes, James D.; Halpern, Wendy G.; Hukkanen, Renee R.; Long, Gerald G.; Meseck, Emily K.; Patrick, Daniel J.; Thibodeau, Michael S.; Wood, Charles E.; Francke, Sabine
The severity grade is an important component of a histopathologic diagnosis in a nonclinical toxicity study that helps distinguish treatment-related effects from background findings and aids in determining adverse dose levels during hazard characterization. Severity grades should be assigned based only on the extent (i.e., amount and complexity) of the morphologic change in the examined tissue section(s) and be clearly defined in the pathology report for critical lesions impacting study interpretation. However, the level of detail provided and criteria by which severity grades are assigned can vary, which can lead to inappropriate comparisons and confusion when evaluating pathology results. To help address this issue, a Working Group of the Society of Toxicologic Pathology's Scientific and Regulatory Policy Committee was formed to provide a "points to consider" article on the assignment and application of pathology severity grades. Overall, the Working Group supports greater transparency and consistency in the reporting of grading scales and provides recommendations to improve selection of diagnoses requiring more detailed severity criteria. This information should enhance the overall understanding by toxicologic pathologists, toxicologists, and regulatory reviewers of pathology findings and thereby improve effective communication in regulatory submissions.